2022
DOI: 10.1186/s40798-022-00530-y
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Risk Factors for Ankle Sprain Differ Between Male and Female Athletes: A Systematic Review and Meta-Analysis

Abstract: Background Ankle sprains remain prevalent across most team sports. However, despite divergent ankle sprain injury rates in male and female athletes, little is known about potential sex-specific risk factors for ankle sprain. Objective To systematically investigate the sex-specific risk factors for ankle sprain. Methods Combinations of the key terms were entered into PubMed, Web of Science, Embase and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 79 publications
0
11
0
1
Order By: Relevance
“…Once again, systematic reviews found a lack of data for female athletes. 24,36 Given our exclusive focus on female soccer players, our results add considerable evidence supporting the risk for LASs in female athletes with prior LASs.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Once again, systematic reviews found a lack of data for female athletes. 24,36 Given our exclusive focus on female soccer players, our results add considerable evidence supporting the risk for LASs in female athletes with prior LASs.…”
Section: Discussionmentioning
confidence: 54%
“…36 Another meta-analysis concluded that a previous ankle sprain was a prognostic risk factor only in male athletes. 24 Despite this, several articles, although few in number, have suggested that an LAS was also a risk factor for 25 found that players with a history of LASs were predisposed to LASs in a prospective cohort study of female collegiate soccer players. Once again, systematic reviews found a lack of data for female athletes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Estimated annual costs to treat these injuries are at least USD 2 billion (in 1984 dollars) [39]. These injuries now occur more frequently in females than males in sports like basketball, soccer, lacrosse, and volleyball [24, 34, 44], so the physical and financial burden of chronic ankle instability is shifting to females.…”
Section: Where Are We Now?mentioning
confidence: 99%
“…Establishing these relationships can provide a holistic neuromechanical understanding of chronic ankle instability that can drive more effective personalized screening programs, injury prevention protocols, rehabilitation techniques, and surgical treatments. As the factors associated with ankle ligament injury can differ between males and females [3,24], injury prevention protocols and treatment algorithms likely need to target sex-specific injury mechanisms.…”
mentioning
confidence: 99%